2019
DOI: 10.1101/745687
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Traction forces control cell-edge dynamics and mediate distance-sensitivity during cell polarization

Abstract: Traction forces are generated by cellular actin-myosin system and transmitted to the environment through adhesions. They are believed to drive cell motion, shape changes, and extracellular matrix remodeling [1][2][3]. However, most of the traction force analysis has been performed on stationary cells, investigating forces at the level of individual focal adhesions or linking them to static cell parameters such as area and edge curvature [4][5][6][7][8][9][10]. It is not well understood how traction forces are … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
3
3
0
Order By: Relevance
“…A cell could further reduce δμ 0 /μ 0 via sensory multiplexing. Indeed, cells have been known to modulate the forces they exert in order to vary the modes they apply, consistent with our predictions for behavior during sensory multiplexing 65 . A cell's spatial resolution is limited by the maximum number of focal adhesions that it can simultaneously apply to the network.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…A cell could further reduce δμ 0 /μ 0 via sensory multiplexing. Indeed, cells have been known to modulate the forces they exert in order to vary the modes they apply, consistent with our predictions for behavior during sensory multiplexing 65 . A cell's spatial resolution is limited by the maximum number of focal adhesions that it can simultaneously apply to the network.…”
Section: Resultssupporting
confidence: 87%
“…In particular, cells can obtain additional information about the stiffness of their environment by applying multiple probes using forces that vary in space and time. Interestingly, such regulation of probes has been found to influence cellular differentiation 73 , and cells in culture have recently been observed to vary the spatial symmetries of forces they exert 65 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the phase-contrast images show, for both cases, that when the cells are more elongated, i.e., polarized, the magnitude of their forces is much higher compared to the forces when they were not polarized. This finding is consistent with previous studies (33,54) that reported that traction forces increase with distance of focal adhesions from the cell center. Possible mechanism for this phenomenon involves protrusion-retraction and actin flow at the cell edge while migrating and polarizing (54).…”
Section: Force and Stiffness Dynamicssupporting
confidence: 94%
“…Recent studies have shown that filamentous NMII localizes to the trailing edge through a mechanism that involves actin retrograde flow [45]. In keratocytes, NMII filaments control traction stress in a manner dependent on the distance to the center of mass of the cell [46], consistent with the aberrant elongation of the cell body observed when NMII-A is deleted [15,17]. By maintaining RLC in a soluble, non-filamentous state, Y155 phosphorylation Article represents a mechanism to maintain a reservoir of exchangeable RLC that can be used by the cell to reassemble NMII filaments and generate traction in response to changes in their microenvironment.…”
Section: Discussionmentioning
confidence: 99%